The Role of Islamic Philanthropy in Post Covid-19 Pandemic Economic Recovery: English - Ahmad Agus Hidayat; Achmad Muzakki (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2023)
This research aims to explain the important role of Islamic philanthropy, which contains elements such as zakat, infaq, shadaqah and waqaf, to make a real contribution to the economic problems caused by the Covid-19 pandemic. This research is a qualitative descriptive method with a library approach, where secondary data is used in the form of research findings, books, journals and articles related to the research topic. Data collection in this research involved literature searches through academic databases, literature selection and data extraction. This research uses literature synthesis analysis, quality evaluation, and conclusion drawing. The results of this research explain that the critical role of Islamic philanthropy in contributing to economic recovery is: (1) The need to establish UPZ in every village in Indonesia (2) Maximization of the cash zakat program along with productive zakat (3) The need to optimize the management of zakat and infaq (4) Providing educational program assistance to students affected by Covid-19, prioritizing Islamic economics students in the hope that they can make a real contribution to society through education or knowledge about Islamic economics. Of course, if several of the programs mentioned can run as expected, the acceleration of Indonesia's economic growth will soon be realized. Â